Faktor - Faktor yang Mempengaruhi Keikutsertaan Warga dalam Posbindu Penyakit Tidak Menular - Fajar Anita Sari; Atik Aryani; Anik Suwarni (JOURNAL SAINS STUDENT RESEARCH, 2026)
Non-communicable diseases (NCDs) are a major health problem that continues to increase and contributes significantly to morbidity and mortality. The Integrated Non-Communicable Disease Development Post (Posbindu PTM) was established as a promotive and preventive effort to control NCD risk factors through community participation. However, community participation in Posbindu PTM activities remains suboptimal. The objective of this study is to analyze factors influencing community participation in Posbindu PTM activities. This study used a quantitative approach with a descriptive correlation cross- sectional design. The population was 110 people. A purposive sampling technique was used, with 81 respondents selected based on inclusion and exclusion criteria. Bivariate data analysis used the chi-square test, while multivariate data analysis used logistic regression. The results show that age, gender, education level, and knowledge were not significantly influence with community participation in the Posbindu PTM (Non- Communicable Diseases Post). Meanwhile, occupation and the role of cadres were significantly influence with community participation. The multivariate analysis shows that employed respondents are 4.6 times more likely to be active in the Posbindu PTM than unemployed respondents. Furthermore, the role of cadres increases the likelihood of community participation by 112.3 times compared to non-supportive cadres. Occupation and the role of cadres were the dominant factors influencing community participation in the Posbindu PTM.